Pengaruh Celebrity Endorser, Perilaku Konsumen Dan Iklan Terhadap Minat Beli Konsumen Pada Produk Avoskin Di Media Sosial Tiktok (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Aisyah Putri Patrisia; Nurhidayah Nurhidayah; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the influence of celebrity endorsers, consumer behavior and advertising on buying interest in Avoskin products on Tiktok social media (Case Study of Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2019). This research includes a type of research with quantitative. The method used is multiple linear regression. The sampling technique uses the formula from Solvin with the calculation results of 86 samples. To solve the problem in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. The variables Celebrity Endorser (X1), Consumer Behavior (X2), Advertising (X3) have a significant simultaneous effect on Buying Interest in Avoskin Products on Tiktok Social Media (Y). And there is a partial influence between Celebrity Endorser (X1), Consumer Behavior (X2), Advertising (X3) on Buying Interest in Avoskin Products on Tiktok Social Media (Y) Keywords: Celebrity Endorser, Consumer Behavior, Advertising, Buying Interest